Genetic imaging of the association of oxytocin receptor gene (OXTR) polymorphisms with positive maternal parenting - Michalska, Kalina J.; Decety, Jean; Liu, Chunyu; Chen, Qi; Martz, Meghan E.; Jacob, Suma; Hipwell, Alison; Lee, Steve S.; Chronis-Tuscano, Andrea; Waldman, Irwin D.; Lahey, Benjamin B. (Frontiers in Behavioral Neuroscience, 2014)
Background: Well-validated models of maternal behavior in small-brain mammals posit a central role of oxytocin in parenting, by reducing stress and enhancing the reward value of social interactions with offspring. In contrast, human studies are only beginning to gain insights into how oxytocin modulates maternal behavior and affiliation. Methods: To explore associations between oxytocin receptor genes and maternal parenting behavior in humans, we conducted a genetic imaging study of women selected to exhibit a wide range of observed parenting when their children were 4-6 years old. Results: In response to child stimuli during functional magnetic resonance imaging, hemodynamic responses in brain regions that mediate affect, reward, and social behavior were significantly correlated with observed positive parenting. Furthermore, single nucleotide polymorphisms (rs53576 and rs1042778) in the gene encoding the oxytocin receptor were significantly associated with both positive parenting and hemodynamic responses to child stimuli in orbitofrontal cortex, anterior cingulate cortex and hippocampus. Conclusions: These findings contribute to the emerging literature on the role of oxytocin in human social behavior and support the feasibility of tracing biological pathways from genes to neural regions to positive maternal parenting behaviors in humans using genetic imaging methods.